Moisture harvesting and water transport through specialized micro-structures on the integument of lizards - Comanns, Philipp; Effertz, Christian; Hischen, Florian; Staudt, Konrad; Böhme, Wolfgang; Baumgartner, Werner (Beilstein Journal of Nanotechnology, 2011)
Several lizard species that live in arid areas have developed special abilities to collect water with their bodies' surfaces and to ingest the so collected moisture. This is called rain- or moisture-harvesting. The water can originate from air humidity, fog, dew, rain or even from humid soil. The integument (i.e., the skin plus skin derivatives such as scales) has developed features so that the water spreads and is soaked into a capillary system in between the reptiles' scales. Within this capillary system the water is transported to the mouth where it is ingested. We have investigated three different lizard species which have developed the ability for moisture harvesting independently, viz. the Australian thorny devil (Moloch horridus), the Arabian toadhead agama (Phrynocephalus arabicus) and the Texas horned lizard (Phrynosoma cornutum). All three lizards have a honeycomb like micro ornamentation on the outer surface of the scales and a complex capillary system in between the scales. By investigation of individual scales and by producing and characterising polymer replicas of the reptiles' integuments, we found that the honeycomb like structures render the surface superhydrophilic, most likely by holding a water film physically stable. Furthermore, the condensation of air humidity is improved on this surface by about 100% in comparison to unstructured surfaces. This allows the animals to collect moisture with their entire body surface. The collected water is transported into the capillary system. For Phrynosoma cornutum we found the interesting effect that, in contrast to the other two investigated species, the water flow in the capillary system is not uniform but directed to the mouth. Taken together we found that the micro ornamentation yields a superhydrophilic surface, and the semi-tubular capillaries allow for an efficient passive – and for Phrynosoma directed – transport of water.
Keywords: capillary; horned lizard; rain harvesting; thorny devil; water transport